Modulation of forelimb and hindlimb muscle activity during quadrupedal tied-belt and split-belt locomotion in intact cats. (2nd April 2015) - Frigon, A.; Thibaudier, Y.; Hurteau, M.-F.
Highlights: EMG was differentially modulated in flexors and extensors of the fore- and hindlimbs during split-belt locomotion. While some changes in EMG could be explained by belt speed, there were also clear dissociations. Split-belt locomotion weakened the relationship between EMG burst durations and kinematic phase durations. Abstract: The modulation of the neural output to forelimb and hindlimb muscles when the left and right sides step at different speeds from one another in quadrupeds was assessed by obtaining electromyography (EMG) in seven intact adult cats during split-belt locomotion. To determine if changes in EMG during split-belt locomotion were modulated according to the speed of the belt the limb was stepping on, values were compared to those obtained during tied-belt locomotion (equal left–right speeds) at matched speeds. Cats were chronically implanted for EMG, which was obtained from six muscles: biceps brachii, triceps brachii, flexor carpi ulnaris, sartorius, vastus lateralis and medial gastrocnemius. During tied-belt locomotion, cats stepped from 0.4 to 1.0 m/s in 0.1 m/s increments whereas during split-belt locomotion, cats stepped with left–right speed differences of 0.1 to 0.4 m/s in 0.1 m/s increments. During tied-belt locomotion, EMG burst durations and mean EMG amplitudes of all muscles respectively decreased and increased with increasing speed. During split-belt locomotion, there was a clear differential modulation of the EMG patterns between flexors and extensors and between the slow and fast sides. Changes in the EMG pattern of some muscles could be explained by the speed of the belt the limb was stepping on, while in other muscles there were clear dissociations from tied-belt values at matched speeds. Therefore, results show that EMG patterns during split-belt locomotion are modulated to meet task requirements partly via signals related to the stepping speed of the homonymous limb and from the other limbs.